AN INVESTIGATION OF DISEASE STATUS IN ORGANIZED AND UNORGANIZED SECTOR OF POULTRY IN UTTAR PRADESH - Khan, Mohd Ameer; Chander, Mahesh (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
The present study was conducted with purposively selected 120 unorganized and 24 organized poultry farmers of Gorakhpur and Bareilly district of Uttar Pradesh (U.P.) to know the disease status in chicken production in U. P. An interview schedule was developed incorporating relevant questions and pretested and modified to final format for data collection. The data were collected from farmers through personal interview and processed by frequency and percentage analysis.
Keywords: Poultry; Organized; Production; Disease